PENGARUH KEPEMILIKAN INSTITUSIONAL, AUDITOR SWITCHING, DAN FINANCIAL DISTRESS TERHADAP AUDIT DELAY: Studi Empiris pada Perusahaan Sektor Pertambangan yang Terdaftar di Bursa Efek Indonesia - Lukita Wahyu Kristiana; Dea Annisa (LPPM Universitas Bina Bangsa, 2022)
This study aims to examine whether institutional ownership, auditor switching, and financial distress have an effect on audit delay in mining sector companies listed on the Indonesia Stock Exchange (IDX) in 2018 to 2020. The type of research conducted is quantitative research using associative methods. The research sample was determined using purposive sampling technique, so that a sample of 34 companies could be produced with a total of 102 observational data. The regression analysis test used was descriptive statistical analysis test, panel data regression model selection, panel data regression model selection test, classical assumption test, panel data analysis and hypothesis testing. The results of the study prove that institutional ownership and financial distress have a significant negative effect on audit delay. Meanwhile, auditor switching has no effect on audit delay